Full Endoscopic Posterolateral Transarticular Lumbar Interbody Fusion Using Transparent Plastic Working Tubes: Technical Note and Preliminary Clinical Results - Du, Yu; Jiang, Fuling; Zheng, Haiyan; Yao, Xudong; Yan, Zhengjian; Liu, Yang; Wang, Liyuan; Zhang, Xintai; Chen, Liang (Frontiers in Surgery, 2022)
Backgroud A series of full-endoscopic lumbar interbody fusions have been reported, but special fusion cages or operating instruments are often needed, and there are many complications in the operation and the learning curve is long. We have used single portal endoscopic system for lumbar interbody fusion in a novel posterolateral transarticular approach, which will take advantage of the incision for pedicle screws insertion and avoid nerve root damage by using a transparent plastic working tube. The purpose of this study was to present the surgical technique of full endoscopic posterolateral transarticular lumbar interbody fusion（FE-PTLIF） and to analyze the preliminary clinical results. Methods 39 patients (17 men and 22 women; mean age [x̅±s] 55.2 ± 12.2 years) have been enrolled in this retrospective study between March 2019 and January 2021 in the 2nd affiliated hospital of chong qing medical university. All patients were treated with full endoscopic lumbar interbody fusion via posterolateral transarticular approach with a transparent plastic working tube. Demographic characteristics, diagnosis, operative time, and estimated blood loss were evaluated. Intraoperative photo and perioperative imaging, were recorded. The preoperative and post-operative clinical data were collected for statistical analysis. Results The preliminary clinical follow-up data achieved good results. No patients had serious postoperative complications and none of these patients required revision surgery during the perioperative or follow-up period.. We compared the visual analogue scale and Oswestry disability index scores before and after surgery. The differences were statistically significant (P < 0.05). The mean total blood loss（including drainage blood）was 54.4±20.3 ml. The mean operative time was 130.5±23.8 minutes. At the last follow-up, the fusion rate of the lumbar intervertebral space was 100%. Conclusions This novel posterolateral transarticular approach and transparent plastic working tube can reduce the difficulty of the operation, so that the conventional intervertebral fusion cage（bullet-shaped polyetheretherketone (PEEK) nonexpandable fusion cage） and surgical instruments can be used in the full endoscopic lumbar intervertebral fusion surgery, which can reduce the cost and improve the efficiency of the operation.